PERAN The Role of Unit IV Intelkam Sat Tuban Police in Early Detection to Prevent Criminal Acts of Theft - Yosinta , Petronela (Advances in Police Science Research Journal, 2024)
This research examines the role of Unit IV of the Intelligence and Security Unit (Satintelkam) of Tuban Police in conducting early detection to prevent motor vehicle theft (curanmor) in East Java. The background of this study is the increasing population in East Java, which contributes to a rise in unemployment, leading to economic hardship within the community. These factors are believed to influence the increase in crime rates, particularly motor vehicle theft. The objectives of this research are: (1) To describe the role of Unit IV Satintelkam of Tuban Police in the implementation of early detection to prevent motor vehicle theft, and (2) To describe the factors that influence Satintelkam in carrying out early detection to prevent motor vehicle theft. To analyze these issues, the author employs several theories, including basic intelligence theory and 6M management theory. The concepts used as the theoretical foundation include the concept of roles, the concept of early detection, the concept of the intelligence security unit, and the concept of motor vehicle theft. This study uses a qualitative method with descriptive analysis to process data and conduct field research to gather direct data through observation. Primary and secondary data sources are utilized, and data triangulation is used to ensure data validity. The focus is on three main activities in early detection efforts: intelligence investigation, intelligence security, and intelligence gathering. The findings of the research are: (1) Unit IV Satintelkam of Tuban Police has carried out several early detection efforts through investigation, security, and gathering, but the implementation in the field has not been fully optimal. (2) The factors influencing the implementation of early detection include internal and external factors, and it was found that the facilities and infrastructure used are inadequate. The conclusions of this study are: (1) The role of Satintelkam in following the existing procedures, specifically Regulation No. 1 of 2023 on the Implementation of Intelligence Operations of the National Police, has not been fully optimal. (2) The factors affecting early detection activities, using the 6M management theory, have been addressed well, but the facilities and infrastructure available to the Satintelkam of Tuban Police are insufficient given the increasingly advanced technology today.